2006
DOI: 10.1242/jeb.02457
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal and chronic salinity tolerances of three freshwater insects: Cloeon sp. and Centroptilum sp. (Ephemeroptera: Baetidae)and Chironomus sp. (Diptera: Chironomidae)

Abstract: . The implications of altered growth rates and changes in developmental times are discussed. This study illustrates the variability in responses to increased salinity, and highlights the need to continue studying sub-lethal and chronic exposures in a range of freshwater invertebrates, in order to predict impacts of salinisation on freshwater biodiversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 23 publications
(34 reference statements)
1
73
1
3
Order By: Relevance
“…However, relationships between sublethal effects and salinity are often non-monotonic, with some freshwater species performing optimally at intermediate salinity [37][38][39]. In contrast, an increase in growth or development was not observed with slightly elevated salinity in three ephemeropteran species [2,35]. EPT DCOH i n c r e a s i n g l y r a r e i n n a t u r e Figure 1.…”
Section: Exposure Durationmentioning
confidence: 99%
“…However, relationships between sublethal effects and salinity are often non-monotonic, with some freshwater species performing optimally at intermediate salinity [37][38][39]. In contrast, an increase in growth or development was not observed with slightly elevated salinity in three ephemeropteran species [2,35]. EPT DCOH i n c r e a s i n g l y r a r e i n n a t u r e Figure 1.…”
Section: Exposure Durationmentioning
confidence: 99%
“…The energy spent in osmoregulation cannot be spent in other metabolic processes, leading to sub-lethal effects on the organImpact of potash mining in streams: the Llobregat basin (northeast Spain) as a case study Rubén isms, e.g. delayed growth (Hassell et al, 2006;Kennedy et al, 2003). When salt concentration is too high the organisms are no longer able to keep the osmotic balance within their cells and they die (Cañedo-Argüelles et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…and Centroptilum sp. (Ephemeroptera: Baetidae) decreases (Hassell et al, 2006); developmental rates and survival are reduced for Chironomus sp. (Diptera: Chironomidae) (Hassell et al, 2006), Aedes taeniorhynchus Wiedemann and Aedes aegypti L. (Diptera: Culicidae) (Clark et al, 2004); and survival is reduced for Culex australicus Dobrotworsky and Drummond and Aedes camptorhynchus Thomson (Diptera: Culicidae) (van Schie, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Ephemeral water bodies are characteristic of the Wheatbelt, where they show a range of salinities, especially in areas affected by secondary salinisation, making them ideal to investigate how salinity affects the colonisation and oviposition behaviour of insects. Numerous studies have investigated how salinity influences the distribution of aquatic organisms by examining patterns in species occurrence (Halse, 1981;Bunn & Davies, 1992;Kay et al, 2001;Williams, 2003;Halse et al, 2004;Marshall & Bailey, 2004;Pinder et al, 2004;Piscart et al, 2005a) and salt sensitivity (Roberts, 1996;Blasius & Merritt, 2002;Kefford et al 2003;Jeffery et al 2005;Hassell et al, 2006;Zalizniak et al, 2006). Studies have found a range of invertebrate fauna, such as the disease vector Ae.…”
Section: Introductionmentioning
confidence: 99%